PENGABDIAN MASYARAKAT TENTANG PEMBEKALAN MANAJEMEN ORGANISASI DALAM KEGIATAN PELANTIKAN DAN ORIENTASI PENGENALAN ORGANISASI DENGAN THEMA BERORGANIASASI DENGAN HATI BERKARYA DENGAN AKSI: Community Service On Provision Of Organizational Management Introduction Activities And Organizational Introduction Orientation With The Theme Organizing With Heart, Working With Action - Yamin, Bahri; Rachman, M. Taufik (Yayasan Al-Amin Qalbu, 2025)
The NTT Student Community Organization in Mataram is formed based on regency, sub-district, and religious origin. These organizations include the Manggarai Mataram Muslim Family Communication Forum (FK2M), the Komodo Boleng Mataram Student and Pupil Association (IMPKBM), and several others. Each organization holds annual routines such as the inauguration of new management and an Organizational Introduction Orientation (OSPOR) for new students who are members of the IMPKBM. The methods used are discussions and lectures. The results are organizational management training at the inauguration and orientation events, with the theme